Lumbar Medial Branch Block Volume‐Dependent Dispersion Patterns as a Predictor for Ablation Success: A Cadaveric Study. Issue 6 (22nd November 2017) - Wahezi, Sayed E.; Alexeev, Edward; Georgy, John S.; Haramati, Nogah; Erosa, Stephen A.; Shah, Jay M.; Downie, Sherry
Abstract: Background: Lumbar facet arthropathy is a common cause of low back pain. Literature supports treatment with radiofrequency ablation (RFA) of associated nerves that innervate lumbar facets when alternative conservative therapies have failed. Diagnostic local anesthetic blocks precede therapeutic ablation, but have a false‐positive rate of 27%‐63%, and some authors have questioned their utility in predicting therapeutic response to RFA. The authors of the current study believe that injectate volume may be a contributing factor to false positivity. Objective: To evaluate the difference in volume dispersion between 0.25 mL and 0.5 mL of injectate when performing lumbar medial branch blocks. We hypothesized that injection volumes greater than 0.25 mL during lumbar medial branch blocks would affect the distal branches of the adjacent medial branches, thus decreasing the specificity of the procedure. Thus, we attempted to demonstrate that injection volumes greater than 0.25 mL during lumbar medial branch blocks would affect the distal branches of the adjacent medial branches, which might increase false positivity of the blocks. Study Design: Cadaveric investigation. Setting: Tertiary care center. Participants: Not applicable. Outcome Measurements: To demonstrate that the spread of lumbar medial branch blocks using commonly injected volume coats adjacent structures that are not affected by radiofrequency ablation. Methods: Six cadavers were chosen with nondissected lumbar spines. Fluoroscopically guided medial branch injections were performed bilaterally using the posterior oblique approach. A volume of 0.25 mL or 0.50 mL of a 9:1 solution of Omnipaque 240 and 1% medical grade methylene blue were delivered to the left and right sides, respectively. Postinjection computed tomographic imaging was performed, followed by dissection. Results: Both volumes adequately coated the medial branches, but in the 0.5‐mL injectate cohort there was consistent spread dorsally to the superficial muscles and distal segments of the dorsal branches distant to the target nerves, whereas in the 0.25‐mL injectate cohort the spread was contained in the deep and intermediate muscular lumbar layers, close to the intended target. Conclusion: We suggest that a 0.5‐mL injectate volume in clinical practice may produce an adjacent‐level nerve block in addition to the intended injection level, thus decreasing the specificity of a targeted lumbar medial branch block. A 0.25‐mL quantity of injectate reliably contacted the lumbar medial branches without extensive extravasation. Presumably, this means that 0.25 mL total volume for a lumbar medial branch block may provide greater specificity for RFA planning. Level of Evidence: NA